Analisis Penerapan Keselamatan Pekerja Terhadap Risiko Bahaya di Pabrik Tahu Sumedang Putri Deli - Fahmi Tegar; Susilawati Susilawati (Yayasan Baru Haji Samsudin, 2023)
Introduction: The manufacturing industry is an industry that processes raw materials into semi-finished materials and finished goods, the application of K3 in tofu factories must be carried out with applicable SOPs including the use of PPE and working hours but there are still many found to be inappropriate, this can lead to work accidents. Research objective: this aims to find out how the application of K3 to the risk of harm to Sumedang Tofu Factory manufacturing workers in Deli Serdang Regency. Methods: This research uses descriptive qualitative, the research object is workers in the tofu factory with a sample of 5 people with data collection techniques, namely in the form of observation, interviews, and documentation. Results: The implementation of OSH in tofu factories has not been maximally implemented even though workers use PPE in the form of aprons and shoes but are not equipped with gloves. For the risk of hazards that occur in the form of working hours > 8 hours, workers exposed to hot water during the cooking process, body postures from activities that are less ergonomic, slippery floor conditions so they can slip, and exposure to hot steam and the temperature of the work environment in the boiling location and frying. Conclusion: The importance of using PPE and providing training and supervising workers in carrying out the production process is to increase worker productivity.